Conversion of butyronitrile to butylamines on noble metals: Effect of solvent on catalyst activity and selectivity - Segobia, Dario Jobino (2014)
The liquid-phase hydrogenation of butyronitrile to butylamines was studied on Pt(0.27%)/SiO2, Pd(0.33%)/SiO2 and Ru(1.80%)/SiO2 using n-butanol, toluene and cyclohexane as solvents. In n-butanol, Pt and Pd catalysts formed preponderantly dibutylamine and minor amounts of tributylamine while Ru/SiO2 yielded mainly butylamine. Replacing n-butanol by toluene or cyclohexane caused significant changes in catalyst activity and selectivity. These changes were interpreted by relating the catalyst performance with the solvent-catalyst interaction strength that was investigated by temperature-programmed desorption of solvents and mass spectrometry. Pd/SiO2 strongly deactivated with the progress of the reaction in all the solvents.